2021
DOI: 10.1371/journal.pone.0251171
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and stresses experienced by athletes and coaches leading up to the Paralympic Games

Abstract: The demands of high-performance sport are exacerbated during the lead up to the Major Games (i.e., Paralympics). The purpose of this study was to better understand the challenges experienced and strategies utilized by Australian athletes (n = 7) and coaches (n = 5) preparing for the Tokyo Paralympic Games using semi-structured interviews. The thematic analysis highlighted challenges specific to participants’ sport (e.g., budgetary constraints, decentralized experiences, athletes with various impairments), pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 59 publications
(84 reference statements)
0
19
0
Order By: Relevance
“…[ 6 ]. Coaching elite para-athletes requires a more adaptive approach (e.g., considering the athlete’s unique abilities) [ 36 ] that may be challenged by remote working. The current data revealed that 16% of the increase in perceived stress during lockdown was associated with sport classification ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ]. Coaching elite para-athletes requires a more adaptive approach (e.g., considering the athlete’s unique abilities) [ 36 ] that may be challenged by remote working. The current data revealed that 16% of the increase in perceived stress during lockdown was associated with sport classification ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…evidenced an increase in alpha activity recorded during the user's volitional resting-state, across MBSR sessions, which was correlated with mindfulness practice and predicted BCI performance [42]. Strategies to reduce challenges and stress when preparing for the competition include anticipation and preparation through detailed planning, including contingency planning, and expectation management, i.e., focusing on the process rather than the outcome [43]. Training in MBSR would t with these approaches to stress management, and enhance BCI task performance under the pressure of competition.…”
Section: Discussionmentioning
confidence: 98%
“…Stieger et al [ 46 ] evidenced an increase in alpha activity recorded during the user’s volitional resting-state, across MBSR sessions, which was correlated with mindfulness practice and predicted BCI performance. Strategies to reduce challenges and stress when preparing for the competition include anticipation and preparation through detailed planning, including contingency planning, and expectation management, i.e., focusing on the process rather than the outcome [ 47 ]. Training in MBSR would fit with these approaches to stress management and enhance BCI task performance under the pressure of competition.…”
Section: Discussionmentioning
confidence: 99%